Development of Waste Fee Management System for Village-Owned Enterprise Using Agile Approach - Fadila Aura Isnaeni; Aditya Dwi Putro; Lisda Lisda (Jurnal Teknologi Informasi dan Multimedia, 2025)
In the era of digital development, effective public services are essential, one of which is in West Mejasem Village through the Spirit Mejabar Village-Owned Enterprise (BUMDes). This research focuses on developing a website-based system that makes it easier for BUMDes administrators to manage waste fees and increase transaction transparency. The system development method uses the agile process, which allows development to be done flexibly and iteratively. The phases in this research include problem identification, literature study, planning, design, development, release, and system review. This system was built using the PHP programming language, Laravel framework, and MySQL as a database. System testing was conducted using the black-box testing method, which resulted in a success value of 97.76%, indicating that the features on the system run well. In addition, the questionnaire results given to users showed a satisfaction level of 90.67%, which scored "Very Good" on a Likert scale. The result of this research is a website that facilitates BUMDes administrators in managing waste fees more efficiently, increases transparency in data management, and is a platform that introduces BUMDes and its services to the community. This system can be an effective solution for managing waste fees in West Mejasem Village and can be implemented.